Ve-eileh divrei David : essays in semitics, Hebrew Bible and history of biblical scholarship - Sperling, S. David. (Culture and History of the Ancient Near East, 2017)
Ve-Eileh Divrei David: Essays in Semitics, Hebrew Bible and History of Biblical Scholarship , covers the career of S. David Sperling, a well-known and respected Biblical scholar. It is divided into three sections representing the three foci of the author's work namely, Semitic philology, Bible, and the history of biblical scholarship. The chapters represent a remarkable 40 years of scholarship and convey deep knowledge of a range of topics that is rarely paralleled in today's scholarship.